Expression of neuroblastoma‐related genes in bone marrow at end of high‐risk neuroblastoma therapy. Issue 9 (20th April 2022) - Asgharzadeh, Shahab; Marachelian, Araz; Villablanca, Judith G.; Liu, Wei Yao; Kennedy, Rebekah; Sposto, Richard; Naranjo, Arlene; Tenney, Sheena; Yu, Alice L.; Ozkaynak, M. Fevzi; Sondel, Paul M.; Park, Julie R.; et al.
Abstract: Background: Minimal disease quantification may predict event‐free survival (EFS) and overall survival (OS). Methods: We evaluated mRNA expression of five neuroblastoma‐associated genes (NB5 assay) in bone marrows (BM) of patients with newly diagnosed high‐risk neuroblastoma who received consistent immunotherapy. mRNA expression of CHGA, DCX, DDC, PHOX2B, and TH genes in BM of 479 patients enrolled on the immunotherapy arm of Children's Oncology Group trials ANBL0032 and ANBL0931 was evaluated using real‐time polymerase chain reaction (PCR)‐based TaqMan low‐density array. Results from end‐consolidation and end‐therapy were analyzed for association with five‐year EFS/OS and patient and tumor characteristics. Tests of statistical significance were two‐sided. Results: NB5 assay detected neuroblastoma‐related mRNA in 222 of 286 (77.6%) of BMs obtained at end‐consolidation and 188 of 304 (61.8%) at end‐therapy. Any mRNA level detected in end‐therapy BM correlated with significantly worse EFS (57% [49.6%‐63.7%] vs 73.0% [63.5%‐80.4%]; P  = 0.005), but not OS. Analysis limited to patients in complete response at end‐therapy still found a significant difference in EFS with detectable versus not detectable NB5 assay results (58.9% [49.5%‐67.1%] vs 76.6% [66.1%‐84.2%]; P  = 0.01). End‐consolidation results did not correlate with EFS or OS. Multivariable analysis determined end‐therapy NB5 assay BM results ( P  = 0.02), age at diagnosis ( P  = 0.002), and preconsolidation response ( P  = 0.02) were significantly associated with EFS independent of other clinical and biological parameters evaluated, including end‐therapy response. Conclusions: If further validated in additional patient cohorts, the NB5 assay's ability to independently predict EFS from end‐therapy could improve patient stratification for novel maintenance therapy trials after current end‐therapy to improve outcome.